QUALITY OF DENTAL SERVICES: ASSOCIATION WITH SOCIODEMOGRAPHIC AND SELF-PERCEPTION CHARACTERISTICS - Silva, Douglas Emanuel Maciel da; Siciliani, Camila Casimiro; Desordi, Juline Manica; Rodrigues, Francini de Oliveira; Colet, Christiane de Fátima; Kolankiewicz, Adriane Cristina Bernat (Cogitare Enfermagem, 2024)
Objective: To associate sociodemographic variables with the self-perception of primary health care users. Method: Cross-sectional study with 222 users of dental services from 15 primary care units in a medium-sized city in Rio Grande do Sul, Brazil. Questionnaires with sociodemographic profile, self-perception, and the Primary Care Assessment Tool Brasil oral health were used. For comparisons of t-Student test scores for independent groups and ANOVA (one way) – Post Hoc Sheffé. Results: Users with lower family income (p=0.016), lower education (p=0.027), and who needed to make or replace dental prostheses (p=0.020) showed a significant association in the attribute of service utilization. Regarding accessibility, the variables toothache (p=0.021) and satisfaction with oral health (p<0.001) showed significant associations. In the information system attribute, the higher the number of queries (p=0.012), the better the score. Conclusion: Significant associations were found between sociodemographic variables and self-perception of oral health with the mean scores.